Thermo-cleavable poly(fluorene-benzothiadiazole) to enable solution deposition of multi-layer organic light emitting diodes - Höfle, Stefan; Kuhn, Marius; Hamburger, Manuel (Organic electronics, 2017)
The design of solution processable multi-layer organic light emitting diodes (OLEDs) is often hampered by the choice of solvents. To avoid the dissolution of the emission layer upon the subsequent deposition of further functional layers, we synthesize and investigate thermo-cleavage in poly[2,7-(3-(9-methyl-9H-fluorene-9-yl)propyl (2-methylhexane-2-yl) carbonate)-alt-4,7-(benzo[c][1,2,5]thiadiazole)] (c-F8BT). Employed in OLEDs, the non-cleaved polymer yields about the same current efficiency as state-of-the-art F8BT. During pyrolysis at 200 °C, the polymer releases its solubility groups, fully maintaining the device efficiency but becoming insoluble. This feature allows to enhance the OLED performance by applying an additional bathophenanthroline hole blocking layer from solution or by incorporating a low-molecular weight electron transport moiety into the affixing polymer matrix.